Factors Affecting Earnings Response Confficient (ERC) in Manufacturing Companies Listed on BEI - Katarina Dyah Kristanti; Luciana Spica Almilia (The Indonesian Journal of Accounting Research, 2019)
This research aims to analyze which factors significantly influence Earnings Response Coefficient (ERC). Sample of this research is including manufacturing companies listed in Indonesia Stock Exchange between period 2012-2016. Sample is drawn using purposive sampling method. There are 280 samples in total that is examined to conduct the study. Multiple regression analysis is used in this research to examine the hypotheses. Independent variables used in this research are earning persistence, profitability, leverage, growth opportunity, firm size, audit quality, CSR disclosure, and conservatism. Result of this research suggests that profitability and firm size have significant and positive influence to Earning Response Coefficient. Result also shows earning persistence and growth opportunity have significant and negative influence to Earning Response Coefficient. Meanwhile leverage, audit quality, CSR disclosure, and conservatism don’t significantly influence Earning Response Coefficient.